The Nurse Role in the Management of ADHD in Children and Adolescent: A Literature Review - Kleve, Liv; Vårdal, Lisa; Elgen, Irene Bircow (Frontiers in Psychiatry, 2022)
Objective To review literature regarding existing and recommended role for nurses in the management of children with ADHD. Method Medline and Cinahl were searched from 2010 to the end of 2019 with the following steps of search: Nurse, ADHD, child* and inclusion criteria published in an English journal and available in the University Library of Bergen. Results Fourty three record were found. However, only five articles scientifically evaluated the nurse role. The nurse role in ADHD management seemed to vary and in this review we found nurses working either independently or as a part of a team with delegated responsibility. Conclusion The literature review gave information to suggest that nurses can have a significant role in providing a range of medical and non-medical interventions, continuity of care and in leading multi-agency collaboration.